Whole exome sequencing analysis of urine trans-renal tumour DNA in metastatic colorectal cancer patients. Issue 6 (13th November 2019) - Crisafulli, Giovanni; Mussolin, Benedetta; Cassingena, Andrea; Montone, Monica; Bartolini, Alice; Barault, Ludovic; Martinetti, Antonia; Morano, Federica; Pietrantonio, Filippo; Sartore-Bianchi, Andrea; Siena, Salvatore; Di Nicolantonio, Federica; et al.
Abstract : Background: The analysis of circulating free tumour DNA (ctDNA) in blood, commonly referred as liquid biopsy, is being used to characterise patients with solid cancers. Tumour-specific genetic variants can also be present in DNA isolated from other body fluids, such as urine. Unlike blood, urine sampling is non-invasive, can be self-performed, and allows recurrent longitudinal monitoring. The features of tumour DNA that clears from the glomerular filtration barrier, named trans-renal tumour DNA (trtDNA), are largely unexplored. Patients and methods: Specimens were collected from 24 patients with KRAS or BRAF mutant metastatic colorectal cancer (mCRC). Driver mutations were assessed by droplet digital PCR (ddPCR) in ctDNA from plasma and trtDNA from urine. Whole exome sequencing (WES) was performed in DNA isolated from tissue, plasma and urine. Results: Out of the 24 CRC cases, only four had sufficient DNA to allow WES analyses in urine and plasma. We found that tumour alterations primarily reside in low molecular weight fragments (less than 112 bp). In patients whose trtDNA was more than 2.69% of the urine derived DNA, cancer-specific molecular alterations, mutational signatures and copy number profiles identified in urine DNA are comparable with those detected in plasma ctDNA. Conclusions: With current technologies, WES analysis of trtDNA is feasible in a small fraction of mCRC patients. Tumour-related genetic information is mainly present in low molecular weight DNA fragments. Although the limited amounts of trtDNA poses analytical challenges, enrichment of low molecular weight DNAs and optimised computational tools can improve the detection of tumour-specific genetic information in urine.